Wide variation in shape of hypoplastic left ventricles undergoing recruitment and biventricular repair: A statistical shape modeling study - Isabel R. Barnet; Noah E. Schulz; Sunil J. Ghelani; David M. Hoganson; Eric N. Feins; Peter E. Hammer; Sitaram M. Emani; Lynn A. Sleeper; Rebecca S. Beroukhim (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Patients with hypoplastic left ventricles (LV) who undergo volume-loading procedures (recruitment, biventricular [BIV] repair) are at risk for adverse outcomes, including heart failure and death. We investigated pre-BIV LV shape as a predictor of outcome after BIV repair in patients with hypoplastic LVs. Methods: Baseline and post-recruitment cardiac magnetic resonance imaging and computed tomography data were analyzed in patients with hypoplastic LV (<50 mL/m2). Statistical shape modeling (SSM) was utilized to generate a model of the shape and variability of LVs. Traditional measures of LV sphericity and eccentricity were also measured. Major adverse cardiovascular events (MACE) included heart failure, transplant, and death. Results: Of 95 patients with baseline mean LV volume 29 ± 13 mL/m2, 45/95 (47%) had a right dominant atrioventricular canal defect, 31/95 (33%) had a variant of hypoplastic left heart syndrome, and 18/95 (19%) had endocardial fibroelastosis (EFE). A wide variation in LV shape was found by SSM, and shape modes were associated with right ventricle (RV) and LV size, and diagnosis. BIV repair was achieved in 74/95 (78%) patients; 13/74 (18%) of BIV patients had MACE. Predictors of MACE following BIV repair included EFE, higher RV mass index, and higher RV end-diastolic volume index. No baseline or post-recruitment LV shape parameter was associated with the outcome after BIV repair. Conclusion: The shape model of hypoplastic LVs demonstrated a wide array of LV shapes. LVs gained sphericity and size and lost eccentricity with recruitment. Though the ventricles changed shape with recruitment, no specific LV shape characteristic at the baseline or post-recruitment stage was predictive of decision to proceed with BIV repair or outcome. Higher RV mass and volume may represent new biomarkers that predict outcomes following BIV repair in patients with hypoplastic LV. Further investigation could determine the reproducibility of these findings.